To orbit and back again : how the space shuttle flew in space - Sivolella, Davide (Springer Praxis Books, 2014)
The question may be simple, but the answer is not as easy to give. This book describes the structures and systems used each time the Shuttle was launched, and then follows an imaginary mission, explaining how those structures and systems were used in orbital operations and the return to Earth. Details of how anomalous events were dealt with on individual missions are also provided, as are the recollections of those who built and flew the Shuttle. Highly illustrated with many diagrams, photographs and technical drawings, To Orbit and Back Again • focuses on the engineering aspects of the Shuttle • describes the systems and subsystems in clear, non-technical terms • brings to the fore the design work behind the Space Shuttle and the mission itself.